CYCLE OF ABUSE IN RUTH ANN NORDIN’S NOVEL HIS REDEEMING BRIDE (2009): A PSYCHOLOGICAL FEMINISM - Parhusib, Christin Natalya (JURNAL LITERARY CRITICISM, 2016)
This research investigated about a woman cycle of abuse in His Redeeming Bride authored by Ruth Ann Nordin. This research has purposes: (1) What are woman circle of abuse in His Redeeming Bride novel; (2) How do the woman face the oppression in the His Redeeming Bride novel. This research is a descriptive qualitative research. The primary data is sentences in His Redeeming Bride novel authored by Ruth Ann Nordin which describes about woman oppression conditions or circumstances. The data were collected by analyzing the sentences which consist of tension building, acute violence, reconciliation/honeymoon and calm mentioned by Dr. Walker.As the result, there are 22 sentences which describes about oppression. The women face the oppression bravely because they think that they need to stay strong and continue to live even though their husband leaves them. Most oppression in the novel indicates the woman suffered from psychological violence. Keywords: Cycle of abuse, women oppression, psychological violence, feminism.